Constructing Dependency: The United States and the Problem of Foreign Oil. (September 2014) - Herbstreuth, Sebastian
Dependence on foreign oil has long been considered a national security issue in the United States. Yet imports from some countries, such as Canada, are seen as a benign form of economic interdependence that yields gains from trade for both parties. Literature on energy interdependence usually conceives of dependency as an objective material condition whose political implications can be accessed through sober cost/benefit analysis. By contrast, this article argues that dependency is best seen as a discourse and that assessments of the costs and benefits of dependency are shaped by cultural constructions of geography. A critical constructivist approach to interdependence is developed to make this case. US dependence on Middle Eastern oil serves as an example to illustrate the argument. It is argued that American representations of the Arab world as America's principal cultural Other have precluded a liberal reading of US–Middle Eastern energy interdependence.